366 Mixed ovary tumor with malignant germinal component and sex cord-stromal, unclassified: presentation of an unusual case. (18th September 2019) - Saenz, J; Medina, M; Beltran, MI; Suescun, O; Almeciga, A; Calderon, P
Abstract : Objectives: Ovarian neoplasm composed of germ cells and elements of the sexual cords, in genetically and phenotypically normal women without the morphology of gonadoblastoma. In 1972, Talerman introduced the term for these neoplasms. Methods: A 14-year-old patient with a history of abdominal pain. Ultrasound evidence of solid abdominopelvic mass with areas of cystic degeneration, diameters 22 x 13 x 10 cm. Antecedent of precocious puberty, menarca at 8 years. Phenotypically without alterations. She was taken to surgery, evidence of right ovarian tumor, predominantly solid, smooth surface, multilobed. Weight 2460 grams, size 24 x 18 x 11 cm. No pelvic or para-aortic adenomegalies. Pelvic cavity without metastatic involvement. The histological report shows mixed tumor of ovary with malignant germinal component and stromal-unclassified sexual cords: endodermal sinus tumor and dysgerminoma (70%) and sexual cord tumor with annular tubules (30%). Stage IA is classified. Receives adjuvant chemotherapy with Bleomycin-Etoposide-Cisplatin scheme for 3 cycles. One year after surgical resection in disease-free period. Results: This is an infrequent neoplasm reported in the literature. Approximately 10% of these tumors have malignant germ cell components compared to 60% of gonadoblastomas. It differs from gonadoblastoma in its macroscopic appearance, histological pattern, absence of regressive changes and occurrence in normal gonads of phenotypic and genetically normal women. Conclusions: This is a very rare neoplasm, the pillar of management being the resection of the gonad that contains the tumor and the conservation of the gonad against the lateral that is normal.